When does a Pringle Maneuver cause harm?. Issue 4 (April 2021) - Fagenson, Alexander M.; Gleeson, Elizabeth M.; Nabi, Fatima; Lau, Kwan N.; Pitt, Henry A.
Abstract: Background: The Pringle Maneuver (PM) is considered to be safe and effective. However, data regarding perioperative outcomes after a PM are conflicting. Therefore, the aim of this analysis is to compare the outcomes of patients who have and have not undergone a PM in North America. Methods: Patients undergoing major (≥3 segments) or partial hepatectomy (≤2 segments) were identified in the 2014–17 ACS-NSQIP hepatectomy database. Patients with and without a PM were compared. Propensity matching was utilized, and subgroup analyses by liver texture, hepatectomy extent and pathology were performed. Results: Prior to matching, 3706 (24%) of 15, 748 hepatectomy patients underwent a PM. The PM was utilized in 1445 (27 %) of major and 2261 (22 %) of partial hepatectomies. After matching, 3295 patients with and 3295 without a PM were compared. Operative time was significantly increased for patients undergoing a PM (246 vs. 225 min, p < 0.001). Subgroup analyses revealed post-hepatectomy liver failure and septic shock to be significantly increased (both p < 0.05) for patients undergoing a PM during a partial hepatectomy or in patients with metastatic disease. Conclusion: Patients undergoing a partial hepatectomy and those with metastatic disease have worse outcomes when a Pringle Maneuver is performed.